Fablehaven : secrets of the dragon sanctuary / 4. - Mull, Brandon, 1974- (Mull, Brandon, 2009)
The magical preserve Fablehaven provides refuge to numerous mystical species: centaurs, trolls, satyrs, ogres, fairies, minotaurs, brownies, imps, nymphs, and many others. But some beings are too large and powerful to be confined to regular enchanted refuges. These mightiest of creatures dwell inside the dragon sanctuaries.